Analisis Strategi Pemasaran Online Dalam Era Digital - Aidatul Fauziah; Anggi Anggraini; Elsa Elitia Hasibuan; Suwandi S (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Online marketing strategy in the digital era, with a focus on reviewing concepts and implementation. Technological developments and changes in consumer behavior have changed the marketing landscape significantly. In this article, we discuss various online marketing strategies that have been implemented by various businesses to face the challenges and opportunities that exist in the digital era. And explore how companies integrate these elements into their marketing strategies. This research also discusses several examples of success and obstacles faced in implementing online marketing strategies. With a deep understanding of the concepts and implementation of online marketing strategies, companies can increase their success in achieving their marketing goals in the rapidly changing digital era.,This research uses library research, namely a method of collecting data by understanding and studying theories from various literature related to the research. This data collection uses the method of searching for sources and constructing them from various sources, for example books, journals and research that has already been carried out. Library materials obtained from various references are analyzed critically and must be in-depth in order to support the propositionsÂ andÂ ideas.